Existence of Solutions of Fractional Differential Equations - Unul, Sinem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This thesis is aimed to study the existence of mild solutions of a class of fractional differential equations with different boundary conditions. By using fixed point theorems, the existence results about mild solutions are expected to obtain. A strong motivation for studing fractional differential equations comes from the fact, that is essential in various fields of science, engineering and economics. Keywords: Differential equations, integral boundary conditions, irregular boundary conditions, p-laplacian operator.

ÖZ: Bu tez farklı sınırlı ko¸sullar altında verilen kesirli diferansiyel denklemlerin çözümleri üzerinde çalı¸smayı amaçlamaktadır. Çözümlerin analitik sonuçları, sabit nokta teoremleri ve uygulamaları kullanılarak bulunmu¸stur. Kesirli diferansiyel denklem çalı¸smalarındaki etkin motivasyon, bu konunun bilim, mühendislik ve ekonomide gereklili˘ginden ileri gelmektedir. Anahtar Kelimeler: Diferansiyel denklemler, integral sınır ko¸sulları, düzensiz sınır ko¸sulları, p-laplasyan operatörü.
Doctor of Philosophy in Applied Mathematics and Computer Science. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2016. Supervisor: Prof. Dr. Nazim I. Mahmudov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Differential Equations; Differential equations; integral boundary conditions; irregular boundary conditions; p-laplacian operator